Measuring health: related quality of life in hemodialysis patients. Psychometric properties of the Missoula-VITAS Quality of Life Index (MVQOLI-15) in Greece - Paraskevi Theofilou; Adamantia Aroni; Maria Ralli; Maria Gouzou; Sophia Zyga (Health Psychology Research, 2013)
Different measuring tools have been used to understand the outcomes of end-stage renal disease (ESRD) therapies. However, survival, cost-effectiveness and quality of life (QOL) are the main parameters to evaluate treatment of ESRD. The current study meant to assess the psychometric properties (reliability and validity) of the Missoula-VITAS Quality of Life Index (MVQOLI-15) translation to Greek in patients undergoing hemodialysis (HD). A total sample of 79 HD patients voluntarily participated in this pilot study. Domain analysis of MVQOLI-15-Greek was conducted based on the collected data at initial assessment. The reliability properties of the instrument were tested using the following measures; internal consistency, repeatability, test-retest reliability and convergent validity. Domain analysis demonstrated that all domains of the questionnaire had good variability. MVQOLI-15-Greek internal consistency was satisfactory with an overall Cronbach’s a at 0.74. Pearson’s r and intraclass correlation coefficient revealed strong correlations (ranging from 0.91 to 0.98) between initial assessment and reassessment. MVQOLI-15-Greek convergent validity analysis indicated that the domains were strongly related to the same construct. The findings of the study indicate that the Greek version of MVQOLI-15 provided satisfactory psychometric properties supporting its use within pathological populations and in the context of national QOL measurement.